Ambient particulate matter (PM2.5) and adverse birth outcomes in Ho Chi Minh City, Vietnam - Tinh Huu Ho; Chinh Van Dang; Thao Thi Bich Pham; To Thi Hien; Supat Wangwongwatana (Hygiene and Environmental Health Advances, 2023)
Exposure to fine particulate matter (PM2.5) has been documented to adversely affect birth outcomes, but the evidence is sparse in developing countries. This study assessed the associations between maternal PM2.5 exposure and adverse birth outcomes, i.e., birth weight (BW) decrease, term low birth weight (LBW), and preterm birth (PTB) in Ho Chi Minh City (HCMC), Vietnam.Between 2016–2019, 163,868 women with singleton pregnancies in HCMC were recruited in the study. The PM2.5 dataset was collected from two available fixed monitoring stations. Five different windows of exposure to PM2.5 were calculated, including the first month of pregnancy, first trimester, second trimester, third trimester, and entire pregnancy. Linear regression was applied to evaluate the association between BW decrease and PM2.5 exposure, and logistic regression was employed to study the risk of term LBW and PTB.The study indicated that prenatal exposure to PM2.5 decreased BW and increased the risk of PTB. Each 10 µg/m3 increase in PM2.5 during the second trimester lowered with 11.771 g the BW (95% confident interval - CI: 5.246 – 18.296), and increased with 23.1% the risk of PTB (Odds ratio – OR = 1.231, 95%CI: 1.136 – 1.336). However, the association between maternal exposure to PM2.5 and the risk of term LBW was not statistically significant.Our study showed that maternal exposure to PM2.5 was associated with lower BW and an increase in the risk of PTB. Reducing exposure to air pollutants, in particular ultrafine particles (PM2.5) for pregnant women will improve infants’ health.